The complete guide to decks. - Black & Decker Corporation (Towson, Md.); Creative Publishing International (Minneapolis, Minn. : Creative Pub. International, 2009)
"Teaches the process of designing, building and maintaining a deck. Includes the latest contemporary options, such as how to work with eco-friendly wood and reclaimed plastic"--Provided by publisher.
At head of title: Black & Decker.
"Includes the newest products & fasteners; add an outdoor kitchen."
Includes bibliographical references and index.
Keywords: Decks (Architecture, Domestic) -- Design and construction -- Amateurs' manuals